The relationship between morning blood pressure surge and left ventricular hypertrophy in newly diagnosed hypertensive patients (Annals of Medical Research, 2021)
Aim: The main aim of this study is to reveal the relationship between the blood pressure surge pattern in newly diagnosed hypertensive patients and left ventricular hypertrophy (LVH).Materials and Methods: 92 patients (60 female, 32 male) were included in the study. Patients who have not been diagnosed with hypertension or even if they have been diagnosed with it, have not received any medication since the last 3 weeks, and who were newly diagnosed with hypertension were included in the study. Morning Blood Pressure Surge (MBPS) was calculated by subtracting the lowest systolic blood pressure recorded during sleep from the systolic blood pressure value of the 2nd hour after awakening.Results: It was observed that 69 patients were nondippers and 29 patients had LVH. As a result of the comparison of LVH groups, it was determined that patients with LVH had higher night time systolic blood pressure values and morning blood pressure surges. In the consequence of the correlation analysis, it was found out that there was a positive correlation between left ventricular mass index and night and 24-hour systolic blood pressure and morning blood pressure surge.  Conclusion: The morning blood pressure surge is a marker and independent predictor of hypertension in terms of cardiovascular incidents and target organ damage. In our study, we found the frequency of LVH to be significantly higher in patients with morning blood pressure surges.